Perspectiva, implementação, gestão e tecnologias da agricultura digital: um estudo de caso aplicado ao agronegócio brasileiro - Manfredo Neto, Leonardo (Universidade Federal de São Carlos, 2023)
The agribusiness has been characterized for being relevant in the Brazilian’s national scenario, in terms of participation in economy, exports and environment. The agriculture 4.0 represents benefits for all society, businesses and corporate governance. The theme has presented lack in conceptual terms regarding its implementation and new conformation paradigms. In this context, the objective of this paper aimed to verify how was the status of its implementation through an empiric approach, by studying a Brazilian agribusiness technology company and, additionally, by investigating the literature and scientific production (national and international), in terms of product development and management strategies. The study combined a systematic literature review with a case study, through exploratory research with qualitative nature, to clarify and delimit the concepts related to this topic. It has been identified issues in reliable bases, previous research have been synthesized and integrated, and it have brought implications of theoretical construct, through an organized and systematized vision. The results of the systematic review and case study, based on the three key concepts established (implementation, management and technology development), and their respective subdivisions into topics, brought the visibility of the state of the art in the academic context, added to the empirical application evidence through the case study in the field. Additionally, the paper contributed to analyze the challenges involving the fourth revolution in agriculture, in terms of planning levels (operational, tactical and strategical), added to the visibility by segments (sugar-energy, grains, forestry, equipment manufacturers) and company sizes, as well as, contributing with innovative concepts on referential agriculture and general index for the agriculture 4.0. Finally, the scores, interpretations and status of all parameters, segments and organizations have been demonstrated and explained, correlating documents, interviews and the applied questionnaire to bring important inferences for the sector. The paper has highlighted future directions for academics and managers to obtain assertive visibility about the most recent technological revolution in the field.
Perspective, implementation, management and technologies of digital agriculture: a case study applied to Brazilian agribusiness
Keywords: Agricultura de precisão; Agricultura 4.0; Agricultura inteligente; Fazenda inteligente; Precision agriculture; Agriculture 4.0; Smart agriculture; Smart farm; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO